After the Final Snap: Cognitive Appraisal, Coping, and Life Satisfaction among Former Collegiate Athletes - Williams-Rice, Brian T. (My University, 1996)
Lazarus and Folkman's (1984) cognitive model was used to examine the effect of retirement from intercollegiate football. Participants included 52 former college football athletes from Division IA and IAA. The questionnaire included the Intercollegiate Football Retirement Questionnaire (IFRQ); demographic information, personal control ratings, and life satisfaction ratings from the Elite Athlete Retirement Interview Schedule (Wethner, 1985); General Emotion Scale (GES, Folkman & Lazarus, 1985), and the 60-item COPE (Carver et al., 1989; Carver & Scheier, 1994) to assess coping strategies. Former players experienced both positive and negative emotions, reported different levels of personal control, and used a variety of coping strategies that were related to life satisfaction. The appraisal process was a stronger predictor of life satisfaction following intercollegiate football retirement, than the use of any specific coping strategy.
Keywords: identity; football; skills